PENGARUH NET PROFIT MARGIN (NPM), CURRENT RATIO (CR), DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Siti Mudawanah; Asep Sopiyan (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2021)
Stock prices are a reflection of the company's performance. Basically, investors measure a company's performance in managing its resources to generate profits. To assess the company's performance, investors need to analyze by using several benchmarks, namely the ratio. this study aims to examine the significant effect of the ratio of Net Profit Margin, Current Ratio and Earning Per Share to the price of food and beverage companies on the Indonesia Stock Exchange (IDX) for the period 2012-2017.This research is empirical research, where the data used in this study is secondary data. The population in this study are food and beverage companies listed on the Indonesia Stock Exchange (IDX) in the period of 2012 to 2017, which amounted to 18 companies. the number of samples used in this study as many as 7 companies with the technique of obtaining samples using purposive sampling. The classic assumption test in this study used the normality test, multicollinearity test, heterocedasticity test and autocorrelation. Data analysis using multiple linear analysis, F test (F test), T test (T test) and test coefficient of determination. Data analysis using the help of SPSS20 software.The research results for Net Profit Margin show a significant value of 0.215 which means there is no significant effect on Stock Prices, Current Ratio shows that 0.001 means that there is a significant effect on Stock Prices, Earning Per Share shows a significant value of 0,000 which means a significant effect on Stock Prices. The determination coefficient shows a value of 56,7% while the remaining 43,3% is influenced by other factors. From the results of the F test (F test) obtained results of 0,000, which means that NPM, CR, EPS simultaneously have a significant effect on stock prices. This research is expected to provide useful information in making investment decisions